Irfan Abdul Hameed Fattah's contribution to islamic thought: with special focus on his book Al-Fikr Al- Dini Fi Muwajahati Tahadiyyat Al-Hadathah - Abdul Rahim, Adibah (2015)
Although the discussion on religious thought and the challenges of modernity is not a new debated issue, it is still relevant to contemporary time. Considering this issue as one of the most significant chapters in the history of modern Islamic thought, Irfan took an initiative to deliberate it in an objective manner. In doing so, he did not study modernity from historical perspective which explored divergent historical facts responsible for its emergence; rather specifically focus on the impact of modernity on religion. The impact of modernity has been experienced both by the West particularly in Jewish and Christian religions, as well as the Muslim world particularly in the Muslim experience. This paper will explore Irfan’s views on diversified philosophical trends which represent main qualitative characteristics of modernity. It will try to answer what are the intellectual challenges of modernity posed by the West, and what are the major religious responses to modernity classified by Irfan.